THE ROLE OF EDUCATIONAL MOTIVATION IN THE TEACHING OF FOREIGN LANGUAGES OF STUDENTS OF THE UPPER CLASS AND ITS THEORETICAL FOUNDATIONS - Kamalova Shakhnoza Mamutovna (Web of Journals Publishing, 2025)
Today, the study of foreign languages is important for everyone. The expansion of international relations, globalization and intercultural dialogue requires knowledge of foreign languages. Especially important is the role of educational motivation in the process of teaching foreign languages of students of the upper classes. Academic motivation is the ability of students to actively participate in the educational process, acquire knowledge and strive to achieve their goals. In order for students to be interested in learning a foreign language, they must first get an understanding of how this language benefits them. The practical benefits of learning a foreign language to students, such as traveling to foreign countries, making new friends, participating in international events, play an important role in increasing motivation.
Keywords: Foreign languages, motivation, international organizations, communication, culture, approaches, factors.